Analisis Pengaruh Pajak Penghasilan Pasal 21 (Pph 21) dan Pajak Bumi Bangunan (PBB) terhadap Realisasi Pendapatan Provinsi Jawa Tengah Tahun 2016-2020 (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of article 21 income tax (pph21) and land building tax (PBB) on the realization of Central Java Province income. The analytical method used is the classical assumption test and hypothesis testing. The data used is time series data per year, namely 2016- 2020 from the official website of the Central Statistics Agency (BPS). The results show that in the f test, the sig value for the effect of Article 21 Income Tax (Pph 21) (X1) and Land Building Tax (PBB) (X2) simultaneously on Central Java Income (Y) is 0.580 > 0.05 and f count 0.724 < f table 19.2 so it can be concluded that H3 is rejected, which means that the variables of Article 21 Income Tax (Pph 21) (X1) and Land Building Tax (PBB) (X2) simultaneously have no effect on Central Java Income (Y).